2021
DOI: 10.1007/s00192-021-04850-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress influences the morphology and function of human uterosacral ligament fibroblasts and activates the p38 MAPK pathway

Abstract: Introduction and hypothesis Pelvic organ prolapse (POP) is a common condition in older women that affects quality of life. Mechanical injury of the pelvic floor support system contributes to POP development. In our study, we aimed to examine the mechanical damage to human uterosacral ligament fibroblasts (hUSLFs) to preliminarily explore the mechanism of mechanical transduction in POP. Methods hUSLFs were derived from POP and non-POP patients. Mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Alteration in Frontiers in Physiology frontiersin.org cell growth may affect the production of collagen, elastic fibres and ECMs and the associated synthesis or turnover, assembly, cross-linking and remodeling. Actually, in our previous study, decrease of collagens (COLI and COLIII) and increase of Bax in mRNA levels was found in POP hUSLFs (Zhu et al, 2021). Pelvic floor relies on the pelvic floor fascia and ligaments for its support, and the main component of the ligaments is collagen.…”
Section: Figurementioning
confidence: 88%
“…Alteration in Frontiers in Physiology frontiersin.org cell growth may affect the production of collagen, elastic fibres and ECMs and the associated synthesis or turnover, assembly, cross-linking and remodeling. Actually, in our previous study, decrease of collagens (COLI and COLIII) and increase of Bax in mRNA levels was found in POP hUSLFs (Zhu et al, 2021). Pelvic floor relies on the pelvic floor fascia and ligaments for its support, and the main component of the ligaments is collagen.…”
Section: Figurementioning
confidence: 88%
“…Fibroblasts are responsible for the secretion and remodeling of ECM in ECM-rich pelvic connective tissues that primarily support the pelvic organs. The disfunction of fibroblasts resulted in a disordered metabolism of collagen and other ECM proteins (40)(41)(42). Therefore, the increased fibroblast apoptosis could result in reduced collagen expression in POP and contribute to the weakness of supportive tissues in POP (40,43).…”
Section: Discussionmentioning
confidence: 99%
“…The disfunction of fibroblasts resulted in a disordered metabolism of collagen and other ECM proteins ( 40 - 42 ). Therefore, the increased fibroblast apoptosis could result in reduced collagen expression in POP and contribute to the weakness of supportive tissues in POP ( 40 , 43 ). In the present study, AGEs promoted the apoptosis of fibroblasts from the non-POP group and aggregated the apoptosis of fibroblasts from the POP group, suggesting that AGEs might be a pathogenesis factor that induced the fibroblast apoptosis in POP.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show that the inhibition of p38 MAPK by SB203580 affects the maturation of super mature vinculin-enriched FAs but significantly attenuates the integrin α5 and αV expression levels. Previously, it was shown that the inhibition of p38 MAPK signaling resulted in the abrogation of stretch-induced cytoskeletal reorganization in mouse wild type-derived and human uterosacral ligament fibroblasts [ 63 , 64 ]. On the other hand, other studies report that the status of FA maturation is associated with the ECM composition as well as with the actin cytoskeleton architecture [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%